2016
DOI: 10.1016/j.micron.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations in salivary glands of Rhipicephalus sanguineus ticks (Acari: Ixodidae) exposed to neem seed oil with known azadirachtin concentration

Abstract: Neem (Azadirachta indica) has attracted the attention of researchers worldwide due to its repellent properties and recognized effects on the morphology and physiology of arthropods, including ticks. Therefore, this study aimed to demonstrate the effects of neem seed oil enriched with azadirachtin on salivary glands of Rhipicephalus sanguineus ticks, targets of great veterinary interest because of their ability to transmit pathogens to dogs. For this, R. sanguineus semi-engorged females were subjected to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…female ticks. The responses were dose‐dependent; i.e., as the azadirachtin concentrations increased, the damages were more aggressive, corroborating Denardi et al () and Remedio et al ().…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…female ticks. The responses were dose‐dependent; i.e., as the azadirachtin concentrations increased, the damages were more aggressive, corroborating Denardi et al () and Remedio et al ().…”
Section: Discussionsupporting
confidence: 80%
“…With specific regard to the species Rhipicephalus sanguineus , it was demonstrated that the damages caused in the female reproductive system would be lethal, preventing the ovaries to produce viable germ cells (able to reach mature stages), and, consequently, produce new individuals (Denardi et al, ). Some authors also performed bioassays exposing the synganglion, salivary glands and the integument of Rhipicephalus sanguineus to different neem formulations (Remedio, Nunes, & Anholeto, ; Remedio et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When crossing the integument of the tick, the substances can reach the haemolymph and act on the internal organs (REMEDIO et al, 2015). Certain substances may affect the salivary glands, consequently impairing the process of concentrating ingested blood and thus hindering the effective absorption of nutrients by the ticks (REMEDIO et al, 2016). There is an important correlation between the tick's digestive and reproductive system and, thus, digestive problems can damage their reproductive capacity (REMEDIO et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Alcoholic concentrate of neem seeds has an antifilarial action against Setaria cervi (Tahir et al, 1998;Mishra et al, 2005). Remedio et al (2016) studied the effects of neem seed oil had azadirachtin against Rhipicephalus sanguineus ticks with demonstration the effects of this plant extract on salivary glands of the ticks, with results that; the cells were distorted, cytoplasmic disorganization, and some endoplasmic changes of its lumen, besides several alteration in mitochondrial membrane. Neem had been utilized as antiparasitic in a few types of ectoparasites and some pests because of its quick action.…”
Section: Discussionmentioning
confidence: 99%